Auditory functional magnetic resonance in awake (nonsedated) and propofol‐sedated children. Issue 5 (9th March 2016) - Gemma, Marco; Scola, Elisa; Baldoli, Cristina; Mucchetti, Marta; Pontesilli, Silvia; De Vitis, Assunta; Falini, Andrea; Beretta, Luigi
Summary: Background: Functional Magnetic Resonance Imaging (fMRI) is often used in preoperative assessment before epilepsy surgery, tumor or cavernous malformation resection, or cochlear implantation. As it requires complete immobility, sedation is needed for uncooperative patients. Objective: The aim of this study was to compare the fMRI cortical activation pattern after auditory stimuli in propofol‐sedated 5‐ to 8‐year‐old children with that of similarly aged nonsedated children. Methods: When possible, children underwent MRI without sedation, otherwise it was induced with i.v. propofol 2 mg·kg −1 and maintained with i.v. propofol 4–5 mg·kg −1 ·h −1 . Following diagnostic MRI, fMRi was carried out, randomly alternating two passive listening tasks (a fairy‐tale and nonsense syllables). Results: We studied 14 awake and 15 sedated children. During the fairy‐tale task, the nonsedated children's blood‐oxygen‐level‐dependent (BOLD) signal was bilaterally present in the posterior superior temporal gyrus (STG), Wernicke's area, and Broca's area. Sedated children showed similar activation, with lesser extension to Wernicke's area, and no activation in Broca's area. During the syllable task, the nonsedated children's BOLD signal was bilaterally observed in the STG and Wernicke's area, in Broca's area with leftward asymmetry, and in the premotor area. In sedated children, cortical activation was present in the STG, but not in the frontal lobes. BOLD signal change areas in sedated children were less extended than in nonsedated children during both the fairy‐tale and syllable tasks. Modeling the temporal derivative during both the fairy‐tale and syllable tasks, nonsedated children showed no response while sedated children did. Conclusions: After auditory stimuli, propofol‐sedated 5‐ to 8‐year‐old children exhibit an fMRI cortical activation pattern which is different from that in similarly aged nonsedated children. Abstract :